Epitope vaccine design for the iraqi infectious Bronchitis strains - ZAHRA M. AL-KHAFAJI (International Journal of Pharma and Bio Sciences, 2018)
Infectious bronchitis virus causes infectious bronchitis in chicken leading to a big failure in poultry industry. It is faced mainly by vaccination, but the outbreaks continue with the emergence of new strains due to high rate of mutations and recombination events. Successful vaccine would retard diseases by triggering both B cell and T cell responses. Due to high variability in the Iraqi strains, one of the most antigenic protein was studied and used to derive B cell and T cell epitopes. Three B cell epitopes were satisfied selection criteria (TNVSNASPNTGGVNT, IYQTQTAQSGYY, DFMYGSYHPKCDFRPETIN), Four epitopes (FNFSFLSSF, FSFLSSFVY, FVYKQSDFM, FMYGSYHPK ) were found to dock with chicken MHC I. Epitopes for helper T cell were also derived (LTNFTFTNVSNASPN, TINIYQTQTAQSGYY, YNFNFSFLSSFVYKQ, NFNFSFLSSFVYKQS) for HLA-DR alleles and others showed high engagement with HLA-DP alleles (FTNVSLVKERFVVYR, VNTMLVLTNFTFTNV, GYYNFNFSFLSSFVY, NFSFLSSFVYKQSDF). The results suggest to used multiple epitopes vaccine to cope with the high antigenic drift of the virus.